LOCAL REFERENDA IN THE SYSTEM OF LOCAL SELF-GOVERNMENT OF UKRAINE AND FOREIGN COUNTRIES: COMPARATIVE AND LEGAL ASPECT - Толкачова, Ірина Анатоліївна; Літвінчук, Богдана Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: performance of comparative and legal analysis of local referenda in the system of local self-government of Ukraine and foreign countries. Methods of research: the basis of research consists of methods of cognition (analysis, synthesis, induction, deduction, analogy, comparison), general scientific methods (empirical research, methods of theoretical cognition) and comparative and legal method. Results: the institution of local referendum is quite common in the countries of Europe and, accordingly, is held in order to solve the most important issues of local significance. It is clear that only in a developed civil society, people are able to take the initiative to put issues of local importance to local referendum in a peaceful, civilized way and to resolve them. According to the analysis of local referendum in other countries, not all issues can be put to local referendum, that puts citizens in a certain framework as to determination of the subject of referendum. In compliance with the research and analysis of the scientific literature, certain problems, related to the local referendum as a mechanism of direct democracy, can be identified. First, local referendum can be a threat to Ukraine’s territorial integrity. It is also possible to use local referendum to legitimize questionable or even illegal decisions of local authorities. At the international, especially European, level, there is a clear trend towards the widest implementation of referenda in public administration. In addition, the lack of a relevant law on local referendum in Ukraine is a factor that negatively affects the effectiveness of territorial communities in solving issues of local importance. Therefore, in our opinion, it is appropriate to adopt the Law of Ukraine «On Local Referenda in Ukraine». Discussion: the role and significance of local referenda; the state of legislation on local referenda in Ukraine.